Re-Circumcision: The Hidden Devil of Female Genitalia Mutilation Case Study on the Perception, Attitudes and Practices of Sudanese Women - Magied, Ahmed M. Abdel; Sulima, El Balah A.; Kawther, Dawood M. (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001), 2002)
Realizing that very little is known about the unique Sudanese practice of re-circumcision (RC), particularly in the published form, the present study was carried out. The main focus of the study included the perception and attitudes of women towards the practice and the reasons behind practicing it with full consideration to the impact of level of education and socio-economic status of the respondents. The data was collected using questionnaires and personal interviews. Data was first analyzed manually in the form of tables of frequencies and percentages. However, for the purpose of discussion statistical analysis using T-Test and Chi-Square test was carried out when necessary. The study came up with the following main conclusions: Irrespective of the significant differences in socio-economic status and educational level, the majority of the respondents from the two studied samples were circumcised (94% in Al Muhandiseen and 90% in Al Fitehab). On the other hand, the positive impact of high educational level and socio-economic status was clearly evident in their attitudes towards the circumcision of their daughters. While 82% of the daughters of Al Fitehab respondents were circumcised, only 50% of the daughters of Al Muhandiseen respondents were circumcised. Irrespective of the level of education and socio-economic status, the respondents of the two female samples practiced re-circumcision (88% in Al Muhandiseen and 76% in Al Fitehab). It was, therefore, concluded that re-circumcision and circumcision as practices are complex social problems, which are mainly connected with some repugnant traditions and to a lesser extent erroneous religious beliefs. Therefore, more extensive and in-depth researches and surveys of scientific quality are necessary to provide a comprehensive data base information to help in designing and modulating effective strategies and efficient and sustainable interventions for abolishing re-circumcision within a comprehensive framework of abolishing FGM practice.